2019
DOI: 10.1016/j.nicl.2019.101665
|View full text |Cite
|
Sign up to set email alerts
|

7T MRI allows detection of disturbed cortical lamination of the medial temporal lobe in patients with Alzheimer's disease

Abstract: Using 7T T2⁎-weighted imaging, we scanned post-mortem hemispheres of Alzheimer patients and age-matched controls to describe the patterns of appearance of cortical lamination on T2*-weighted MRI in the medial temporal lobe and to assess the changes in Alzheimer patients versus controls. While controls showed a hypointense line of Baillarger in the majority of the cases, appearance of cortical lamination varied to a greater extent in the Alzheimer patients. Severely distorted cortical lamination was also observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
6
24
0
Order By: Relevance
“…However, the authors failed to found the same difference in the inferior temporal cortex which, on the other hand, reported iron levels correlating with antecedent cognitive decline in those individuals who had underlying plaque and tangle pathology 37 . Total iron levels are known to increase in different brain areas of AD cases 28 , with the temporal cortex being one of the most and earliest affected regions 24,38 . It is not yet clear what the underlying phenomena leading to brain iron accumulation in the context of AD are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors failed to found the same difference in the inferior temporal cortex which, on the other hand, reported iron levels correlating with antecedent cognitive decline in those individuals who had underlying plaque and tangle pathology 37 . Total iron levels are known to increase in different brain areas of AD cases 28 , with the temporal cortex being one of the most and earliest affected regions 24,38 . It is not yet clear what the underlying phenomena leading to brain iron accumulation in the context of AD are.…”
Section: Discussionmentioning
confidence: 99%
“…All donors gave written informed consent for the use of their tissue and medical records for research purposes. The AD cases were selected based on pathological reports (Braak stage 5 or higher) and the appearance of hypo-intense bands and/or foci on the T 2 *-weighted MRI images of the contralateral hemisphere of the same subject 24 . Details of the subjects' demographic are found in Table 1 Each tissue block contained predominantly grey matter.…”
Section: Tissue Selectionmentioning
confidence: 99%
“…And it was found out that there is a large amount of activated iron-containing microglia around Aβ plaques (Kroner et al, 2014;van Duijn et al, 2017). Additionally, cortical iron deposition is increasingly recognized as a novel imaging marker for AD diagnosis through using high field magnetic resonance imaging (MRI) to scan hemispheres of AD patients (Peters et al, 2015;van Duijn et al, 2017;Bulk et al, 2018;Kenkhuis et al, 2019). And cerebral quantitative susceptibility mapping (QSM), an MRI method sensitive to brain iron, reveals that the brain iron burden is elevated in AD patients, combined with Aβ positron emission tomography (PET), which indicates that brain iron load is positively associated with Aβ deposition-related cognitive decline, suggesting that iron may combine with Aβ to exacerbate the cognitive function damage.…”
Section: Iron Metabolism Linking With Ad Pathologymentioning
confidence: 99%
“…305,[307][308][309][310][311] Histological analyses of the cortex of AD patients reveal that the accumulation of iron deposits is also associated with alterations in the pattern of cortical lamination and in myelination changes. 311,312 Consistent with elevated brain iron being an early event in AD pathogenesis, secreted ferritin, which reflects intracellular iron load, is elevated in the CSF of cognitively normal individuals with mild cognitive impairment (MCI). In these pre-AD individuals, the increase either precedes or correlates with Ab pathology, reduced fluorodeoxyglucose utilization, and most importantly, progression to AD thereafter.…”
Section: Age-associated Neurodegenerative Diseasesmentioning
confidence: 99%